PENGARUH CASH RATIO, DEBT TO EQUITY RATIO, DAN RECEIVABLE TURNOVER TERHADAP RETURN ON ASSETS PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018 - Rafida Khairani; Kristianus Buulolo; Mesra Juliana; Yoseph Setiawan Zai (Idaarah: Jurnal Manajemen Pendidikan, 2020)
The increased of cash ratio, debt to equity, receivable turnover is not always followed by an increase and decrease in return on assets. Using that statement as the background of this study, this study is conducted to test the influence of cash ratio, debt to equity, receivable turnover on return on assets. The data collection techniques in this study were conducted using documentation techniques with a sample count of twenty-three (23) and one hundred three (103) populations in food and beverage companies listed on the Indonesia Stock Exchange for the period 2014-2018 using multiple linear analysis techniques. The benefit of the results of this study is a consideration for companies and the next researcher about the variables used in this study. Based on the results of the study can be partially concluded cash ratio, debt to equity, receivable turnover negatively effects on the return on assets and simultaneously positively effects on the return on assets in food and beverage companies listed on the Indonesia Stock Exchange for the period 2014-2018.